Optical properties of silicon carbide obtained by direct ion deposition - Lopin, A.V.; Semenov, A.V.; Puzikov, V.M.; Trushkovsky, A.G. (Functional Materials, 2006)
Optical transmission, absorption and reflection spectra of silicon carbide thin films deposited on sapphire substrate from the carbon and silicon ionic flows have been investigated. The films have been obtained at various deposition paramenters, i.e., under variation of ion energy and substrate temperature. The behavior of optical characteristics of silicon-carbide films depending on influence of changes in technological parameters. It has been shown that direct ion deposition method provides a control of film optical parameters within a wide range.